2022
DOI: 10.3390/polym15010089
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Development Approaches through Wooden Adhesive Joints Design

Abstract: Over recent decades, the need to comply with environmental standards has become a concern in many industrial sectors. As a result, manufacturers have increased their use of eco-friendly, recycled, recyclable, and, overall, more sustainable materials and industrial techniques. One technique highly dependent on petroleum-based products, and at the edge of a paradigm change, is adhesive bonding. Adhesive bonding is often used to join composite materials and depends upon an adhesive to achieve the connection. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 111 publications
0
1
0
Order By: Relevance
“…Also, the density of the toughened samples was measured after the curing process of the bio-adhesive. The results indicated that the average density of the reference wood was 0.56 ± 0.03 g/cm 3 and that the bio-adhesive increased the wood density by 4%.…”
Section: Toughened Substratementioning
confidence: 99%
See 2 more Smart Citations
“…Also, the density of the toughened samples was measured after the curing process of the bio-adhesive. The results indicated that the average density of the reference wood was 0.56 ± 0.03 g/cm 3 and that the bio-adhesive increased the wood density by 4%.…”
Section: Toughened Substratementioning
confidence: 99%
“…The recent concerted drive towards reducing the impact of fossil-based products has spurred the development and increasingly larger adoption of bio-based materials [1][2][3]. This endeavor seeks to usher in a more sustainable era, where the utilization of tree and plant-derived products assumes a pivotal role.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A very recent review on bio-adhesives and their use in wooden adhesive joints can be found in Ref. [44].…”
Section: Bio-adhesivesmentioning
confidence: 99%
“…The worldwide demand for sustainability and green economy leads to significant research interest in the field of biomacromolecular technology in different directions. These include the replacement of fossil-derived polymers with neat biomacromolecules or their derivatives, the use of green synthesis processes in order to recover and/or synthesize monomers derived from renewable resources, and the production of novel eco-friendly, biodegradable polymers based on these monomers [2]. Eco-friendly processes to recover bio-based monomers from biomass and bio-based polymer recycling methods are also of great interest.…”
mentioning
confidence: 99%